2016
DOI: 10.3733/ca.2016a0005
|View full text |Cite
|
Sign up to set email alerts
|

Managing for soil health can suppress pests

Abstract: A "healthy" soil can be thought of as one that functions well, both agronomically and ecologically, and one in which soil biodiversity and crop management work in synergy to suppress pests and diseases. UC researchers have pioneered many ways of managing soil biology for pest management, including strategies such as soil solarization, steam treatment and anaerobic soil disinfestation, as well as improvements on traditional methods, such as reducing tillage, amending soil with organic materials, and cover cropp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
1
8
0
1
Order By: Relevance
“…The current study suggests that the minimum dataset of soil health indicators for Central Washington orchards should include measurements of water availability (AWC, % sand) and of root health (bean root health rating, Pratylenchus nematodes) as well as fertility indicators to meet stakeholder management goals. In contrast other studies of annual crops identified soil health factors related to soil C. Active carbon, and total soil carbon were related to yield in four studies [ 22 , 30 32 ] as well as WSA [ 31 , 33 ] and respiration [ 30 ] in some studies. Soil health indices which focus on environmental processes and response to management [ 10 , 17 ] or median values from regional datasets [ 18 , 19 , 21 ] also include soil carbon, mineralizable N, BD, and fertility indicators.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The current study suggests that the minimum dataset of soil health indicators for Central Washington orchards should include measurements of water availability (AWC, % sand) and of root health (bean root health rating, Pratylenchus nematodes) as well as fertility indicators to meet stakeholder management goals. In contrast other studies of annual crops identified soil health factors related to soil C. Active carbon, and total soil carbon were related to yield in four studies [ 22 , 30 32 ] as well as WSA [ 31 , 33 ] and respiration [ 30 ] in some studies. Soil health indices which focus on environmental processes and response to management [ 10 , 17 ] or median values from regional datasets [ 18 , 19 , 21 ] also include soil carbon, mineralizable N, BD, and fertility indicators.…”
Section: Resultsmentioning
confidence: 89%
“…Appropriateness of soil health assessment tools varies by region, cropping system and management goals. However currently, few soil health assessment tools have been evaluated in perennial crops in the irrigated region of Western North America [ 22 ]. Assessment tools have generally been tested for annual crops and in the rainfed Mid-west, Northeast and Mid-Atlantic [ 5 , 17 , 23 27 ] with only a few tools assessed in irrigated annual crops [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with support from the California Strawberry Commission, the U.S. Department of Agriculture (USDA) and DPR, researchers have developed and tested several nonchemical approaches to the elimination of soil pathogens. These include solarization, steam sterilization, biofumigation with mustard seed meal, and anaerobic soil disinfestation (ASD), all of which have shown some promise (Daugovish et al 2016;DPR 2013;Hodson and Lewis 2016;Koike and Gordon 2015). Many growers in the sample, including nine who remained conventional growers solely, had tried or were considering trying nonchemical alternatives to fumigation.…”
Section: Land Value Is Obstacle To Changementioning
confidence: 99%
“…In contrast, the few growers we interviewed who used more diversified farming methods to control pathogens were much more satisfied with the results. Along with growers, field trial researchers have found effective pest suppression with rotations of plants with biofumigation properties, such as brassicas, along with cover crops and composting, especially in 3to 4-year cycles (Hodson and Lewis 2016;Lloyd 2015;Muramoto et al 2014). The problem, however, with any nonchemical alternative that requires growers to rotate strawberries with a lower value or no-value crop, especially over several years, is that lease costs are generally based on an expectation that strawberries will be grown on an annual basis, not be a minor crop in an integrated diversified system.…”
Section: Land Value Is Obstacle To Changementioning
confidence: 99%
“…Through reliance on biological processes to build healthy soils and support above and below ground biodiversity, diversified systems offer potential GHG emission reductions (through, for instance, application of on-farm sources of organic matter residues from plants and animals rather than fossil fuel-based fertilizers, carbon storage in woody plants, and more efficiency in nutrient management due to crop rotations). Also, resilience to climate perturbations can occur by spreading economic risks across multiple farm products (Jackson et al 2011) and by relying on on-farm resources and biodiversity, with less dependence on synthetic fertilizer and pesticides to improve soil and crop health (Gurr et al 2003;Hodson and Lewis 2016;Suddick et al 2010). Other environmental co-benefits can include more efficient use of water, improved water and soil quality, pest reduction or suppression, or enhancement of wildlife habitat and biodiversity.…”
Section: Integrated and Diversified Farming Systemsmentioning
confidence: 99%